"It began with me": an exploration of exemplary school counselor and principal experiences with LGBT students. Issue 4 (1st October 2020) - Beck, Matthew J.
Abstract: The purpose of this study was to provide insight to the lived advocacy experiences of principals and school counselors who received state and/or national recognition for their work on behalf of lesbian, gay, bisexual, and transgender (LGBT) students. I identified three themes and related subthemes regarding the meaning derived across the participants' advocacy experiences on behalf of LGBT students. The first theme was "It began with me" with subtheme (a) knowing your school. The second theme was advocacy identity with subthemes (a) being a role model, and (b) taking a stand. The third theme was credibility and confidence with subtheme (a) giving back. These findings provide school counselors and principals with stories and practical examples from exemplary and dedicated professionals regarding how to create safer school environments for LGBT students.